Análise experimental do escoamento ao redor de um modelo simplificado de trem de pouso de nariz - Santos, Denner Sávio (2019)
The main purpose of this work was to analyze the air flow around a nose landing gear, experimentally, to better understand and determine its aerodynamic characteristics. The typical configuration of an Airbus A320 aircraft was selected as a reference and a simplified nose landing gear model was used as a baseline. The nose landing gear was completely modeled using CATIAV5R19® and a 1/6 scale was applied due to the size of the wind tunnel. The model was built using a 3D printer and tested in the low-speed wind tunnel with Reynolds number around 5 × 10^5, from the Experimental Aerodynamics Research Center (CPAERO), located at the Federal University of Uberlândia (UFU). The emphasis in this experiment was to visualize the pressure distribution on the landing gear wheel and to evaluate the drag coefficient. Experimental data were collected through anemometry, pressure transducer, aerodynamic balance and visualization techniques. The velocity profiles were acquired from these data, which can be used as reference for an initial validation of numerical analysis. Flow visualization made it possible to identify recirculation regions and the point of detachment of the boundary layer over the nose landing gear.